Indicators of Services of General Interest in EU regional context: between the need to measure and the lacking of their meaning - Eduarda Marques da Costa; Pedro Palma; Daniel Rauhut; Alois Humer; Daniela Constantin; Xabier Velasco (European Regional Science Association (ERSA), 2012)
An indicator is a measure of synthesis, thus representing an abstraction of a situation. Therefore, the indicators can have different functions, from offering the possibility to describe a situation, to the ability to simplify and measure that same situation being, par excellence, a means of communication (HOERNIG and SEASONS, 2004, quoting Innes, 1990 and Hoernig, 2001). Their utility is crucial to a great variety of scientific studies, typically in spatial planning and cohesion analysis, therefore, it's in this way that they are used to study the Services of General Interest in the SeGI project (ESPON) – Indicators and perspective for services of general interest in territorial cohesion and development. Services of general interest are seen as "a key element in the European model of society" and are defined as 'market and non-market services which public authorities class as being of general interest and subject to specific public service obligations'. (EC: 2001/C17/04). This definition is too wide and a classification of 6 main domains (infrastructure, ICT Telecommunication, labor market, education, care services and social housing) was proposed. The Eurostat data for regional scale is very limited in number, availability and regional coverage. In this paper a literature review of more than 35 documents have been done in order to understand regional differentiation and the most effective indicators to evaluate the effects of services of general interest. The analysis show common problems that emerges in EU level. A first aspect is related to differential accessibility to the SEGI. We find a territorial differentiation in the supply of SEGI for each of the domains, where different questions and thematic emerges. Linked to infrastructure domain, question that is highlighted in literature review points to: density, length and rate of use of motorways and railways lines, air traffic, but specially, accessibility to flights. In health theme, literature review points to the question of provision of services, namely in low density and rural areas. But more important is the social accessibility conditions, that depends on persons category and also to the continuity and quality of the services. Despite the difficulties with information availability, the discussion is need, in particular in the present context of crises and political changes conducting to privatization of social services. The role of social services to cohesion in unquestionable as regional European inequalities shows. This paper has been financed by the ESPON applied research project 2013/1/16 Indicators and Perspectives for Services of General Interest in Territorial Cohesion and Development as part of Activity 6. The economic support from ESPON is gratefully acknowledged. The content in this paper does not necessarily reflect the opinion of the ESPON Monitoring Committee.
Keywords: 330